Mental Retardation affects quality of life in families of disabled children and role of nursing practices: A review - D. Khare, Sumit (International Journal of Nursing Research, 2023)
A family with mental retardation child faces a number of challenges such as physical problems, emotional stress, psychological disturbances, family problems, and an additional financial burden for family. Parents may suffer from mental worries because of having a child with mental retardation, family need should be focused on early building and strengthening the social support systems families should focused early intervention programs. Mental retardation is a disability characterized by significant limitations, both in intellectual functioning and in adaptive behavior, as expressed in conceptual, social, and practical adaptive skills, the disability originating before the age of 18. In the USA, mental retardation prevalence has been reported between 0.3% and 3.0%; with a prevalence of 1.0% most studies using administrative or population-based data. In India, the prevalence rates for mental retardation in the school population and the general population, rural and urban, based on psychiatric morbidity survey ranges from 0.1 to 140. Mental retardation affects quality of life including many factors and variables influencing and interacting with its core concepts. Research shows that mothers caring for a child with an intellectual disability have less social and psychological support, have an increased chance of suffering a stressful life event and are more likely to be functioning in an unhealthy family. In this review, we will discuss we will discuss different factors prevalence of mental retardation and its role on quality of life. Role of nurses in improving quality of life is also discussed.